ANALISIS HUKUM EKONOMI SYARIAH TERHADAP JUAL BELI MELALUI MEDIA ONLINE DI KALANGAN MASYARAKAT - Samiya, S; Jelita, J; Riswanda, Neli; Astri, Winda Mely (Jurnal Ekonomi & Bisnis, 2024)
This article discusses the analysis of Islamic law on buying and selling online. This research is literature and qualitative research. Data were collected through books, journals, and documents and analyzed descriptively. The study results conclude that buying and selling online is a sale and purchase transaction of goods carried out by two parties, namely the seller and the buyer, through the internet. In Islamic law, buying and selling online is legal, and the contract is valid on the condition that the goods purchased are halal and have precise specifications, the goods to be bought are following their needs. The buyer has the right to cancel or accept if the goods are not following the order. The sale and purchase are considered fi hukm ittihad al-majlis (in the position of one assembly). Ittihad al-majlis can be interpreted in three ways, namely ittihad al-makan (one place) and ittihad al-zaman (time of time), and ittihad al-haiah (one position). With modern communication media, it is possible to unite two places that are far apart, so that the two places are considered to be one (taaddud al-makan fi manzilah ittihad al-makan). Online buying and selling transactions carried out in two far apart areas are included in ittihad almajlis in the ittihad al-zaman category (one time).Islam allows buying and selling online as long as there is no element of fraud between the two parties in the contract. It has fulfilled the conditions and pillars following the provisions of Islamic law.